Nigerian Agricultural Export and Economic Growth: An Empirical Analysis - J, David I.; S, Mathew; U, Adehi M. (Darul Yasin Al Sys, 2025)
As the world continues to be unpredictable, the need for diversification of a nation's exports, especially for developing countries like Nigeria, cannot be overstated. This study was designed to examine the nexus between agriculture exports and economic growth in Nigeria using secondary data from 1991 to 2020. Using the Augmented Dickey fuller test, co-integration analysis, error correction, and Granger causality analysis, the results revealed that the covariates were stationary (I) and that there is a significant long-run co-integrating relationship between agricultural exports and economic growth (p values <0.05). The results further revealed that about 86% of the variation in agriculture exports was explained by the predictor variables (economic growth). The model diagnostic check revealed that the estimates were not spurious as the errors were linear, not serially correlated, and homoscedastic (all p-values > 0.05). However, there was not enough evidence of a causal relationship between economic growth and agricultural exports, though it was found that there was causality between population growth and the unemployment rate. The study recommends, among others, that employment and security be provided for Nigerians.